BACK STOPPING: CULTIVATION OF HEALTHY VEGETABLES BY USING OF THE ORGANIC WASTE IN URBAN AREAS - Dwie Retna Suryaningsih; Ristani Widya Inti (International Journal of Engagement and Empowerment, 2022)
As part of the community that has household activities, this element of society also produces waste in the form of very much waste. Daily food waste and tree leaves are the most dominating among the community, posing a severe problem. One way to minimize the negative impact caused by domestic organic waste is to process the waste by involving the community. Waste management is a systematic, thorough and sustainable activity that includes waste reduction and handling. Waste management needs to be done comprehensively and integrated from upstream to downstream to provide economic benefits, be healthy for the community, and safe for the environment, and change people's behavior. One way to minimize the abundant amount of waste is to use organic waste to make compost. This method of community service implementation uses the participatory society method and the persuasive approach method. As a result of this activity, the community is very enthusiastic about managing organic waste into compost. In addition, people can cultivate vegetable crops at home by using homemade compost media. The community gets a positive value from this activity, namely a clean and healthy environment, and can be an economic value from processing organic waste into compost